Trends in pediatric central nervous system tumor incidence in the United States, 1998-2013 - Withrow, Diana R. (Cancer Epidemiol Biomarkers Prev, 2018)
BACKGROUND: Brain and other central nervous system (CNS) cancers are the leading cause of US pediatric cancer mortality. Incidence trends can provide etiological insight. We report trends in incidence rates of pediatric malignant CNS cancers and pilocytic astrocytoma (non-malignant but historically registered) in the US. METHODS: Age-standardized incidence rates and annual percent changes (APCs) in rates during 1998–2013 were calculated for children aged 0–19, stratified by subtype, age, sex, and for gliomas, histology and location. We estimated the absolute change in number of cases diagnosed US-wide during 2013 compared to the expected number of cases had 1998 rates remained stable. RESULTS: Rates of all pediatric malignant CNS cancer combined (n=18,612) did not change (APC:0.16, 95% confidence interval [CI]: −0.21,0.53). There were statistically-significant changes in several sub-types, however: glioma incidence (n=10,664) increased by 0.77%/year (95% CI:0.29,1.26), embryonal cancer rates (n=5,423) decreased by 0.88%/year (95% CI: −1.33, −0.43) and pilocytic astrocytoma rates (n=6,858) increased by 0.89%/year (95% CI:0.21,1.58). Of the 1,171 malignant tumors and 450 pilocytic astrocytomas diagnosed in US children in 2013, we estimated 120 excess gliomas, 94 excess pilocytic astrocytomas, and 72 fewer embryonal CNS tumors than would be expected had 1998 rates remained stable. CONCLUSIONS: The gradual changes in incidence we observed for specific types of pediatric CNS cancers are likely due to a combination of changes in classification and diagnosis and true changes in CNS cancer. IMPACT: Continued surveillance of pediatric CNS tumors should remain a priority given their significant contribution to pediatric cancer deaths.